Fluorescence Response Profiling for Small Molecule Sensors Utilizing the Green Fluorescent Protein Chromophore and Its Derivatives - Lee, Jun-Seok; Badridge, Anthony; Peng, Suihan; Yang SiQiang; Kim, Yun Kyung; Tolbert, Laren M.; Chang, Young-Tae (AMER CHEMICAL SOC, 2011)
Using a fluorescence response profile, a systematic examination was performed for synthetic chromophores of the green fluorescent protein (GFP) to discover new small molecule sensors. A group of 41 benzylideneimidazolinone compounds (BDI) was prepared and screened toward 94 biologically relevant analytes to generate fluorescence response profiles. From the response pattern, compounds containing aminobenzyl and heteroaromatic cyclic substructures revealed a pH dependent emission decrease effect, and unlike other fluorescence scaffolds, most BDIs showed fluorescence quenching when mixed with proteins. On the basis of the primary response profile, we obtained three selective fluorescence turn-on sensors for pH, human serum albumin (HSA), and total ribonucleic acid (RNA). Following analysis, a fluorescence response profile testing four nucleic acids revealed the alkyloxy (Ph-OR) functional group in the para position of benzyl analogues contributes to RNA selectivity. Among the primary hit compounds, BDI 2 showed outstanding selectivity toward total RNA with 5-fold emission enhancement. Finally, BDI 24 showed selective fluorescence increase to HSA (K(d) = 3.57 mu M) with a blue-shifted emission max wavelength (Delta lambda(em) = 15 nm). These examples of fluorescence sensor discovery by large-scale fluorescence response profiling demonstrate the general applicability of this approach and the usefulness of the response profiles.
Keywords: HUMAN SERUM-ALBUMIN; ULTRAFAST VIBRATIONAL SPECTROSCOPY; LIVING CELLS; ROSAMINE LIBRARY; GFP-CHROMOPHORE; PROTON-TRANSFER; COMPLEMENTATION; VISUALIZATION; DISCOVERY; MERCURY